2019
DOI: 10.1111/1753-0407.12922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variants of 50 genes on diabetes risk among the Chinese population born in the early 1960s

Abstract: BackgroundGenome‐wide association studies have identified loci that significantly increase diabetes risk. This study explored the genetic susceptibility in relation to diabetes risk in adulthood among a Chinese population born in the early 1960s.MethodsIn all, 2129 subjects (833 males, 1296 females) were selected from the cross‐sectional 2010 to 2012 China National Nutrition and Health Survey. Fifty diabetes‐related single nucleotide polymorphisms (SNPs) were detected. Two diabetes genetic risk scores (GRSs) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…PTDM occurs frequently after kidney transplantation and may be associated with graft loss, so factors that may increase the risk of this complication are being sought. Previous studies have shown that the pathophysiological changes leading to the development of PTDM are similar to those in type 2 diabetes mellitus [ 7 , 8 , 22 , 23 ]. It is believed that the risk factors leading to the occurrence of PTDM include factors associated with the development of type 2 diabetes mellitus, such as obesity, metabolic syndrome and a family history of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTDM occurs frequently after kidney transplantation and may be associated with graft loss, so factors that may increase the risk of this complication are being sought. Previous studies have shown that the pathophysiological changes leading to the development of PTDM are similar to those in type 2 diabetes mellitus [ 7 , 8 , 22 , 23 ]. It is believed that the risk factors leading to the occurrence of PTDM include factors associated with the development of type 2 diabetes mellitus, such as obesity, metabolic syndrome and a family history of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the similar pathogenesis of PTDM and type 2 diabetes, risk factors are currently being sought among the genetic polymorphisms associated with the development of type 2 diabetes [ 7 ]. Among them are polymorphisms in genes encoding enzymes involved in carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…50 Although several suicide prevention activities or strategies have been implemented, strategies proven effective in reducing suicide rates, such as early intervention for youth with mental health disorders, are often not available. Only through a comprehensive and in-depth investigation on the genetic architecture, biomarkers and comorbidities, can the high-risk population at pre-diagnostic or prodromal or asymptomatic stages be targeted, [51][52][53][54][55] and clinical patients can be classified 56 and be treated individually. 50 57 Currently, Korea has implemented a suicide report system with the information mainly provided by the teachers who have a suicidal student.…”
Section: Family-based Programmesmentioning
confidence: 99%
“… 7 , 8 , 9 GRK5 has been identified as a T2D susceptibility gene by genome-wide association study (GWAS). 10 , 11 , 12 , 13 , 14 A variant of GRK5 is associated with the therapeutic efficacy of insulin secretagogue, repaglinide, in those with T2D, 15 and with plasma LDL-cholesterol levels. 16 Germline Grk5 knockout mice displayed mildly impaired glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%